2020
DOI: 10.1590/1980-5373-mr-2020-0314
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Surface Treatments Effect on the Creep Behavior of Ti-6Al-4V Alloy

Abstract: This paper compares the creep behavior of Ti-6Al-4V alloy after different surface treatments, the plasma nitriding using Plasma Enhanced Chemical Vapor Deposition (PECVD), and the deposition of SiC thin films with Cr interlayer using High Power Impulse Magnetron Sputtering (HiPIMS). A microstructural characterization was performed with Scanning Electron Microscopy (SEM), Scanning and Transmission Electron Microscopy (STEM), and Energy Dispersive Spectroscopy (EDS) techniques. The creep test was performed at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The authors observed improved adhesion with increased interlayer thickness of the PACVD-deposited TiN coating compared to the PVD-deposited coating. Jian et al [ 33 ] reported the effect of variation in N content on the structural properties of TiN coating deposited using CVD. The results revealed an increase in lattice parameter with the increase in N content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors observed improved adhesion with increased interlayer thickness of the PACVD-deposited TiN coating compared to the PVD-deposited coating. Jian et al [ 33 ] reported the effect of variation in N content on the structural properties of TiN coating deposited using CVD. The results revealed an increase in lattice parameter with the increase in N content.…”
Section: Literature Reviewmentioning
confidence: 99%